2000
DOI: 10.1097/00000539-200005000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Blood Flow and Function in Elderly Patients Undergoing Laparoscopic Cholecystectomy

Abstract: Laparoscopic cholecystectomy (LC) has been widely accepted as an alternative to laparotomy and has many advantages, including short hospital stay and very limited surgical invasion. However, this procedure may impair hepatic function in elderly patients because high pressure is maintained in the peritoneal cavity for an extended period. We observed the effect of pneumoperitoneum on the middle hepatic venous blood flow (MHVBF) in elderly patients undergoing LC. LC patients were anesthesized with inhaled and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 2 publications
5
50
1
Order By: Relevance
“…Intermittent positive-pressure ventilation and pneumoperitoneum during laparoscopic surgery mechanically decrease hepatic blood flow (4). In addition, traction on abdominal viscera may cause reflex dilatation of splanchnic veins and thereby lower hepatic blood flow.…”
Section: Reduced Hepatic Blood Flow Hypoxemia and Altered Drug Metamentioning
confidence: 99%
“…Intermittent positive-pressure ventilation and pneumoperitoneum during laparoscopic surgery mechanically decrease hepatic blood flow (4). In addition, traction on abdominal viscera may cause reflex dilatation of splanchnic veins and thereby lower hepatic blood flow.…”
Section: Reduced Hepatic Blood Flow Hypoxemia and Altered Drug Metamentioning
confidence: 99%
“…In contrast, laparoscopic surgery usually requires a pneumoperitoneum, which can disrupt respiratory or cardiovascular performance during the operation [13][14][15], and these effects could be more significant in elderly patients with a higher likelihood of preoperative comorbidities and reduced functional capacities [16,17]. Although several studies found no significant difference in the incidence of postoperative complications between elderly and younger patients undergoing LAG [18][19][20][21], severity of complications was poorly defined in most of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanism for elevation of liver enzymes after laparoscopic abdominal surgery is likely due to the increased intra-abdominal pressure and its effects on portal venous flow. The 11-15 mm Hg of CO2 that is used is higher than the normal portal pressure of 7-10 mm Hg, resulting in reduced portal blood flow (11,12) . Free radicals are generated at the end of a laparoscopic procedure, possibly as a result of an ischemiareperfusion phenomenon induced by the inflation and deflation of the pneumoperitoneum (13) , which can damage the Kupffer and endothelial cells of the hepatic sinusoids resulting in increase in liver enzymes postoperatively.…”
Section: Discussionmentioning
confidence: 99%